FORENSICS AUDITING TECHNIQUES AND AUDIT QUALITY OF PUBLIC SECTOR ESTABLISHMENTS IN NIGERIA (Journal of Contemporary Issues in Accounting, 2023)
This study examined the effect of forensics auditing techniques on the audit quality of Ministry, Department and Agencies (MDAs) in Abia State, Nigeria. The proxy for independent variables include computer cross drive, network audit trail and live analysis, while dependent variable is audit quality. The research instrument used was questionnaire and the population of study was made up of staff of MDAs in Abia State from which 100 staff were purposively selected. Multiple regression models were employed for data analysis and testing of hypotheses. The results of the findings revealed that 77%, 86% and 85% of the independent variables respectively variations of audit quality are attributable to the variations in computer forensics techniques. The study concludes that computer forensics techniques have positive and significant effect on audit quality of MDAs in Abia State. The researchers therefore, recommend that Computer forensics procedures need to be followed during investigation and experts like the Certified Public Accountants should be engaged. Also, training of accountants on computer forensics will enable them obtain required skills for investigation of high profile crime prevalent among public office holders. The government needs to support induction and work related training, particularly for employees involved in internal control system and the financial regulations. The MDAs should take advantage of the modern accounting and auditing software to enhance efficiency and smooth operation of government business.
Keywords: Information Technology; forensics auditing techniques; MDAs; Audit quality; Forensic evidence gathering techniques